Knowledge, Attitude and Practices of General Population Regarding Hepatitis A & E Prevention and Control - Sumera Jabeen, Farhan Mukhtar, Sidra Farooq, Hafiza Sidra Ambreen, Muhammad Bilal, Gullelala Bashir (Pakistan Journal of Medical & Health Sciences, 2022)
Aims: To assess the knowledge and attitude of general population, regarding Hepatitis A & E. and practices of study participants to adopt healthy lifestyle for the preclusion of hepatitis A & E. Study Design: Cross sectional study. Place and Duration of Study: Shaikh Zayed Medical Complex, Lahore, and Mayo Hospital Lahore from 1st November 2021 to May 2022. Methodology: Two hundred and fifty individuals were enrolled. A face to face interview of all study participants was conducted and a questionnaire was filled. Results: There were 98 (39.2%) males and 152 (60.8%) females. Majority of the subjects were more than 30 years old. Two hundred and seventeen (87%) and 212 (85%) had correct knowledge about causative agent and treatment of hepatitis A and E respectively. Two hundred and fifty (100%), 213 (85.2%), 190 (76%) and 165 (66%) were having good practices of washing hands after using toilet, good food hygiene, washing fruits and vegetables before eating and avoid contact with person infected with hepatitis A & E respectively. It was observed that age ≥30 years (P=0.000), higher education (P=0.016) and good practices (P=0.000) were significantly associated with good knowledge of participants regarding hepatitis A and E. Conclusion: The participants having better awareness regarding spread and transmission of hepatitis A and E can improve practices regarding prevention and control of disease. The awareness and prevention control programs should be initiated and guidelines regarding personal hygienic practices should be developed and disseminated through mass media. Keywords: KAP study, Hepatitis A, Hepatitis E, Prevention of hepatitis, Control of hepatitis